Acute‐on‐Chronic Liver Failure: A Distinct Clinical Syndrome That Has Reclassified Cirrhosis. Issue 5 (20th December 2019) - Perricone, Giovanni; Jalan, Rajiv
Abstract : Watch a video presentation of this article Watch the interview with the author